Face‐like configurations modulate electrophysiological mismatch responses. (3rd January 2021) - Galigani, Mattia; Ronga, Irene; Bruno, Valentina; Castellani, Nicolò; Rossi Sebastiano, Alice; Fossataro, Carlotta; Garbarini, Francesca
Abstract: The human face is one of the most salient stimuli in the environment. It has been suggested that even basic face‐like configurations (three dots composing a downward pointing triangle) may convey salience. Interestingly, stimulus salience can be signaled by mismatch detection phenomena, characterized by greater amplitudes of event‐related potentials (ERPs) in response to relevant novel stimulation as compared to non‐relevant repeated events. Here, we investigate whether basic face‐like stimuli are salient enough to modulate mismatch detection phenomena. ERPs are elicited by a pair of sequentially presented visual stimuli (S1‐S2), delivered at a constant 1‐s interval, representing either a face‐like stimulus (Upright configuration) or three neutral configurations (Inverted, Leftwards, and Rightwards configurations), that are obtained by rotating the Upright configuration along the three different axes. In pairs including a canonical face‐like stimulus, we observe a more effective mismatch detection mechanism, with significantly larger N270 and P300 components when S2 is different from S1 as compared to when S2 is identical to S1. This ERP modulation, not significant in pairs excluding face‐like stimuli, reveals that mismatch detection phenomena are significantly affected by basic face‐like configurations. Even though further experiments are needed to ascertain whether this effect is specifically elicited by face‐like configuration rather than by particular orientation changes, our findings suggest that face essential, structural attributes are salient enough to affect change detection processes. Abstract : We found a selective mismatch detection modulation induced by basic face‐like configurations, but not by other basic geometric configurations, revealing that only face‐like stimuli are salient enough to modulate the activity of the conflict monitoring system.